Dendropanoxide Attenuates High Glucose-induced Oxidative Damage in NRK-52E Cells via AKT/mTOR Signaling Pathway - Lee, Song Hee; Kim, Ju Ri; Shin, Joo Kyung; Lee, Jin-Sol; Kim, Young Mi; Kwak, Jeong Hwan; Kim, Hyung Sik (Planta Medica, 2024)
Hyperglycemia is a potent risk factor for the development and progression of diabetes-induced nephropathy. Dendropanoxide (DPx) is a natural compound isolated from Dendropanax morbifera (Araliaceae) that exerts various biological effects. However, the role of DPx in hyperglycemia-induced renal tubular cell injury remains unclear. The present study explored the protective mechanism of DPx on high glucose (HG)-induced cytotoxicity in kidney tubular epithelial NRK-52E cells. The cells were cultured with normal glucose (5.6 mM), HG (30 mM), HG + metformin (10 µM), or HG + DPx (10 µM) for 48 h, and cell cycle and apoptosis were analyzed. Malondialdehyde (MDA), advanced glycation end products (AGEs), and reactive oxygen species (ROS) were measured. Protein-based nephrotoxicity biomarkers were measured in both the culture media and cell lysates. MDA and AGEs were significantly increased in NRK-52E cells cultured with HG, and these levels were markedly reduced by pretreatment with DPx or metformin. DPx significantly reduced the levels of kidney injury molecule-1 (KIM-1), pyruvate kinase M2 (PKM2), selenium-binding protein 1 (SBP1), or neutrophil gelatinase-associated lipocalin (NGAL) in NRK-52E cells cultured under HG conditions. Furthermore, treatment with DPx significantly increased antioxidant enzyme activity. DPx protects against HG-induced renal tubular cell damage, which may be mediated by its ability to inhibit oxidative stress through the protein kinase B/mammalian target of the rapamycin (AKT/mTOR) signaling pathway. These findings suggest that DPx can be used as a new drug for the treatment of high glucose-induced diabetic nephropathy.
Keywords: Dendropanax morbifera (Araliaceae); hyperglycemia; dendropanoxide; high glucose; advanced glycation end-product; reactive oxygen species